The last devil to die - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club mystery, 2023)
"Shocking news reaches them--an old friend has been killed, and a dangerous package he was protecting has gone missing. The gang's search leads them into the antiques business, where the tricks of the trade are as old as the objects themselves. As they encounter drug dealers, art forgers, and online fraudsters--as well as heartache close to home--Elizabeth, Joyce, Ron, and Ibrahim have no idea whom to trust. With the body count rising, the clock ticking down, and trouble firmly on their tail, has their luck finally run out?"--